Cerebrospinal Fluid Leak Presenting as Epiphora. Issue 2 (March 2016) - Jain, Sachin; Patel, Rakesh M.; Hage, Ziad; Lim, Janet; Lee, Samuel; Amin-Hanjani, Sepideh; Setabutr, Pete; Aakalu, Vinay K.
Abstract : A 52-year-old woman underwent a right frontotemporal craniotomy for microsurgical clip obliteration of a ruptured right dorsal variant ophthalmic segment carotid aneurysm. During the craniotomy, a defect involving the orbital roof was inadvertently created. The patient was noted postoperatively to have fluid egressing from her OD. The fluid was analyzed and based on glucose and chloride levels was determined to be cerebrospinal fluid (CSF). CT scan of the head demonstrated the orbital roof defect created during surgery. After placement of a lumbar drain, fluid egress from the eye significantly decreased, further confirming the suspicion for CSF leak. Patient was found to have a conjunctival defect of the OD, approximately 2.5 cm × 1.5 cm, extending to the fornix from 9 to 12 o'clock. The conjunctival defect and fornix were repaired with an amniotic membrane graft and a temporary tarsorrhaphy with subsequent resolution of CSF egress. The case report is in compliance with the Health Insurance Portability and Accountability Act. Abstract : Supplemental Digital Content is available in the text.